Cochaperone binding to LYR motifs confers specificity of iron sulfur cluster delivery - Maio, Nunziata (Cell Metab, 2014)
Iron-sulfur (Fe-S) clusters, pre-assembled on the ISCU scaffold, are transferred to target proteins or to intermediate scaffolds by a dedicated chaperone-cochaperone system. However, the molecular mechanisms that underlie substrate discrimination and guide delivery of nascent clusters to specific subsets of Fe-S recipients are poorly understood. Here, we identified interacting partners of the cochaperone HSC20, and discovered that LYR motifs are molecular signatures of specific recipient Fe-S proteins or accessory factors that assist Fe-S cluster delivery. In succinate dehydrogenase B, two LYR motifs engage the ISCU-HSC20-HSPA9 complex to aid incorporation of three Fe-S clusters within the final structure of Complex II. Moreover, we show that members of the LYR motif family which assist assembly of Complexes II or III, SDHAF1 and LYRM7 respectively, are HSC20 binding partners. Our studies unveil a network of interactions between HSC20 and LYR motif-containing proteins that are key to the assembly and function of Complexes I-III.